As relações de gênero no espaço da educação física escolar no município de Pio XII – MA - LIMA, Rarielle Rodrigues (2015)
In this dissertation I propose understand gender concepts of teachers physical education, on the ways direct the systematization of the contents of the practical classes in the city of Pios XII, given the prominence it has practicality in discipline, differing attitudes and practices based on gender, since historically, the construction of the discipline was permeated by discourses that consider sexual difference as natural stuck on the genitals, in line discourses of biology, medicine, psychiatry etc. This delimitation has guided activities and content taugh in school physical education. I make use of the ethnographic method and participant observation techiniques, semi-open interveiwes and focus groups to acquire information on the break-in period in the city of Pius XII, which involved teachers, students and managers between August 2014 and March 2015. I use me of Scott's contributions (1995), Butler (2003, 2004), Louro (2002, 2003), Foucault (1987, 2012), Luz Jr (2001, 2002), Romero (1990; 2001) Daolio (1995), Oliveira (1996); Kunz (1993), Darido et. al. (2001) among others for discussions that permeate the spaces of school physical education highlighting the social relations of genres produced and reproduced in "doing physical education" at school.